Microeconomics - Pindyck, Robert S. (Pearson, 2018)
Microeconomics exposes readers to topics that play a central role in microeconomics. From game theory and competitive strategy, to the roles of uncertainty and information, and the analysis of pricing by firms with market power, the text helps you understand what’s going on in the world of business. It also shows you how microeconomics can be used as a practical tool for decision-making and for designing and understanding public policy.